Thermal state and evolving geodynamic regimes of the Meso- to Neoarchean North China Craton - Guozheng Sun (Nature Portfolio, 2021)
Constraining the thermal state of the lithosphere is crucial to understanding geodynamic regime in early Earth. Here the authors reconstruct ~2.9–2.5 Ga thermal structure of continental lithosphere of the North China Craton using TTG and propose a systematic Archean geodynamic evolution process.